HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG FASILITAS KESEHATAN DENGAN PEMILIHAN PENOLONG PERSALINAN DI KELURAHAN LEKOBALO KECAMATAN KOTA BARAT KOTA GORONTALO - Rena Lihawa; Harismayanti Harismayanti (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Maternal mortality in countries that are growing, especially in Indonesia, is still very high. According to BKKBN data that the maternal mortality rate in Indonesia is the highest in Asia, which is 360 per 100,000 maternal deaths from childbirth. Further it is said that the high maternal mortality rate in Indonesia is still high due to the habits of mothers who gave birth with the help of traditional birth attendants. The purpose of this study was to determine the relationship of knowledge to the selection of pregnant women in the village birth attendants Lekobalo West City District of Gorontalo.The study design used is descriptive and analytical research methods research is conducted with the main objective to create a picture / relationship about a situation objectively. The population consists of 61 people with the sampling method by total sampling. Data were collected using a questionnaire then the results were analyzed by Chi-Square test.The survey results revealed that there is a relationship between maternal knowledge with the selection of village birth attendants in Gorontalo city Lekobalo as evidenced by the chi-square value nilaiχ2 count of 39 361 with a significance value (Asymp.Sig. (2-sided) of p = 0.002 (p > 0:05. Based on the results of the data analysis it can be concluded that there is a relationship between the knowledge of pregnant women with birth attendants in village elections Lekobalo Gorontalo city.